2019
DOI: 10.1155/2019/2316271
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Numerical Simulation of Seawater Intrusion under the Influences of Tidal Fluctuation and Groundwater Exploitation in Coastal Multilayered Aquifers

Abstract: The dynamic behavior of groundwater flow and salt transport is affected by tide and pumping in coastal multilayered aquifers. In this paper, two groups of experiments were conducted considering different constant head inland boundaries. The fluctuation of the groundwater level and the process of seawater intrusion in the multilayered aquifers were observed. A two-dimensional SEAWAT model is developed to simulate the seawater intrusion to coastal aquifers under the influences of tidal fluctuation and groundwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…In the process of seawater intrusion, the external parameters such as local precipitation, pumping quantity, sea level and other related parameters such as permeability parameters and dispersion have an important impact on seawater intrusion. Laboratory experiments have shown that the differences in permeability parameters of different layers will cause different seawater intrusion in the multi-layered aquifers [21]. However, the reason for the differences in seawater intrusion between every two layers is not only the permeability parameters in the field.…”
Section: Sobol Global Sensitivity Analysis Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the process of seawater intrusion, the external parameters such as local precipitation, pumping quantity, sea level and other related parameters such as permeability parameters and dispersion have an important impact on seawater intrusion. Laboratory experiments have shown that the differences in permeability parameters of different layers will cause different seawater intrusion in the multi-layered aquifers [21]. However, the reason for the differences in seawater intrusion between every two layers is not only the permeability parameters in the field.…”
Section: Sobol Global Sensitivity Analysis Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) indicated that freshwater is directly nonpotable when it is mixed with about 1% volume of seawater (250 mg/L chloride) [13]. There are two kinds of inducement factors for seawater intrusion, including natural factors (sea level rising, drought and tide) and human factors (groundwater pumping and mariculture) [14][15][16][17][18][19][20][21][22][23]. Compared with the minor equilibrium damage caused by sea level rise, seawater intrusion caused by a large imbalance of hydraulic gradient due to over-pumping groundwater is more important [1,18,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations